PENENTUAN KADAR ALKOHOL PADA PEMINUM ALKOHOL DENGAN METODE ALCOHOL SALIVA STRIP TEST - Dianita Apriyanti; Siti Nurfajriah; Maulin Inggraini; Noor Andryan Ilsan (Jurnal Mitra Kesehatan, 2023)
Alcohols are organic compounds containing hydroxyl functional groups. The alcohol content in the drink is ethanol. Alcohol poisoning is often associated with injuries from falls, fires, drowning, overdose, sexual abuse, work accidents, traffic accidents, and abusive relationship. This study aims to determine the level of alcohol in alcoholics using the Alcohol Saliva Strip Test method. The type of research used is descriptive with purposive sampling technique and cross-sectional approach and. Specimen collection and examination of the alcohol content in the respondent's saliva were carried out in March 2021 at Kp X, Depok City, West Java Province. The number of respondents was 28 people. The inclusion criteria for this study was alcoholic drinkers aged 17-25 years. The study exclusion criteria were using mouthwash, consuming ascorbic acid such as vitamin C, and having a history of gout. The specimen used in this research was saliva. The method is detected for alcohol content of the respondents used the RightSign brand Alcohol Saliva Strip Test. The results showed the age of the respondents who drank the most alcohol in the range of 17-19 years was 57%. The characteristics of respondents based on the frequency of alcohol consumption are highest in the frequent category (3 times a week or more) as much as 68%. The results showed 71% of the respondents positively drank alcohol and 29% of the respondents were negative. The lowest alcohol content in the respondent's saliva was 0.02% and the highest was 0.08%. The alcohol content in the saliva of the respondents who last drank alcohol 1 week ago was undetectable. This study concludes that the percentage of respondent who detected alcohol in their saliva was 71% and the highest alcohol content in the respondent's saliva is 0.08%. This study also shows that the period, alcohol concentration, and type of alcohol consumed can influence Blood Alcohol Concentration (BAC).